BIBLIOMETRIC ANALYSIS OF STUDIES ON TOURIST GUIDANCE WITH VOSVIEWER - Arpacı, Suat (My University, 2025)
The objective of this study is to present a visual illustration of the current issues pertaining to the field of tourist guiding through a bibliometric review of studies conducted between 2003 and 2023. This study is based on a comprehensive review of the existing scientific literature on the subject. The objective of this study is to identify significant research gaps in existing studies on tourist guiding and to provide guidance for future research in this field. A comprehensive analysis of the literature on tourist guiding was conducted through bibliometric methods. A total of 490 articles published in the Web of Science database were subjected to analysis with the assistance of the VOSviewer software program. The analyses conducted using the tabs 'Co-authorship, Co-occurrence and Citation' revealed the identity of prominent authors, countries and sources. Consequently, the authors with the greatest number of publications on tourist guidance, the most frequently cited authors, the most frequently cited co-authors and publications, the most frequently occurring keywords, the most frequently occurring co-authors, the countries of origin of the authors and the sources of the publications were identified. Furthermore, the analysis revealed a notable increase in publications on tourist guidance.
Keywords: Vosviewer; Web of Science; Bibliometric Analysis; Tourist Guiding